Employee Performance Measurement Analysis Using Information Technology Approach - Erniza; Fahmi; Faisal (Universitas Mulia, 2018)
Industrial revolution of the 4.0 era, the industry began to touch the virtual world in the form of human, machine, and data connectivity. This term is known as the internet of things. The development of information technology today has an excellent influence on the development of Science. The era of the industrial revolution 4.0 marked by this development has made technology one of the tools that can help humans to achieve their goals. With the development of Information Technology currently has penetrated various sectors, such as the office sector in the field of public services, the service sector is one area to measure general satisfaction. In this field, employees are one of the spearheads that function to carry out their responsibilities. Apart from the rapid and rapid development of Information Technology, employees who provide services still do not have an accurate and comprehensive performance measurement system by community expectations and the vision and strategy of the institution's leadership. For this reason, an evaluation technique or method is needed to evaluate the work results of employees, to get maximum results, one of the methods used is a measurement method with the IT Balanced Scorecard approach. The technique itself is a system that has 4 (four) perspective methods at work, while the system is: User Orientation, Company Contribution, Operational Excellence, Maximum. Expectations with a performance measurement system using the IT Balanced Scorecard method to improve the evaluation and assessment system in performance measurement to be able to produce data that can be used in the management process of improving employee performance in institutions in the future.